Enzymatic hydrolysis of microalgal cellulose for bioethanol production, modeling and sensitivity analysis. (15th September 2018) - Shokrkar, Hanieh; Ebrahimi, Sirous; Zamani, Mehdi
Graphical abstract: Highlights: Kinetic and sensitivity study of the enzymatic hydrolysis of microalgal cellulose. Sensitivity analysis showed that k 3 ′ and km3 are the most influential parameters. Microalgae loading strategy is a simple method to increase sugar concentration. Fermentation of concentrated sugar medium from hydrolysis step was performed. Abstract: A kinetic model was developed to describe the enzymatic hydrolysis of microalgal cellulose. In the kinetic model, the factors including product inhibition, temperature, and pH were considered. This model combined two reactions for hydrolyzing algal cellulose to cellobiose and glucose and one reaction for cellobiose breakdown to glucose. Results showed that the highest glucose yield (57%) was achieved at microalgal biomass concentration of 50 g/L, pH 5, and temperature of 50 °C. Moreover, the sensitivity analysis was carried out on each kinetic model parameter. This analysis indicated that k 3 ′ and km3 in reaction R3 (cellobiose to glucose) are the most influential parameters during enzymatic hydrolysis of algal cellulose. Finally, the microalgal biomass loading experiment demonstrated that cellulase could be used thrice without compromising on the glucose yield. Fermentation of concentrated sugar medium with Saccharomyces cerevisiae produced ethanol (12.87 g/L) with yield (0.46 g ethanol/g glucose).